Strategi Pengembangan Usaha Minyak Nilam dalam Upaya Meningkatkan Pendapatan Masyarakat di Nagari Sarik Kecamatan Luhak Nan Duo Kabupaten Pasaman Barat - Rosi Aulia Rahmah; Sandra Dewi (Lembaga Yasin AlSys, 2026)
Although strategies for developing the patchouli oil business to increase community income have received attention in a number of studies, studies that specifically examine empirical conditions at the local level, particularly regarding price fluctuations, technological limitations, and their impact on community income, remain limited. This study aims to describe the strategy for developing the patchouli oil business in an effort to increase community income in Nagari Sarik, Luhak Nan Duo Subdistrict, West Pasaman Regency. This study employed a qualitative approach with a field research design, involving a number of informants consisting of patchouli farmers selected through purposive sampling. Data were collected through interviews, observation, and documentation, and were then analyzed using data reduction, data display, and conclusion drawing techniques. The results showed that the development of the patchouli oil business was influenced by significant price fluctuations, limitations of distillation equipment that remained traditional, high production costs, as well as pest disturbances and weather factors. Farmers’ income varied depending on land area and production yield, but the net profit obtained was relatively small after deducting production costs. These findings contribute to the development of the concept of business development strategies in the community-based agribusiness sector while broadening understanding of patchouli oil business management at the local level. This study concludes that improving production quality, technological innovation, and institutional support are important factors in increasing community income. The implications of this study include theoretical contributions to the development of Islamic economics and practical contributions for the government and the community in formulating sustainable business development strategies, while also opening opportunities for further research related to market aspects and the patchouli oil supply chain.